The impact of leadership style on employees' job satisfaction: a case study in bank of ceylon, sri lanka - Wickramasinghe, P.N.N.; Padmasiri, M.K.D. (University of Jaffna, 2016)
Acquiring and preserving talent is the most vital challenge facing the banking industry. In order to gain the competitive advantage through those employees their performance should be efficient and effective. Accordingly, for that purpose they should be well satisfied. Leadership style is one of the most important factors affecting organizational success and it is a significant aspect of management which will increase and determine the level of job satisfaction. The purpose of this study was to examine the impact of leadership style (LS) and job satisfaction (JS) among junior executive officers (JEO) in Bank of Ceylon Head Office, Sri Lanka. Data was collected through structured questionnaire and convenience sample techniques was used to collect data from 65 junior executive officers (Sample Size) working in Bank of Ceylon Head Office. The construct leadership style consists transactional (TRC) and transformational (TRF) leadership while job satisfaction construct includes extrinsic and intrinsic job satisfaction. The findings of the study show that overall impact of leadership and job satisfaction had only 16% and transformational leadership had 24% impact on job satisfaction. Further, there is a positive and moderate relationship of 40.4% between leadership style and job satisfaction, and transformational leadership and job satisfaction also had a 48.5% of positive and moderate relationship, while transactional leadership and job satisfaction had a strong negative relationship. Findings were concluded that Bank of Ceylon able to enhance employees' satisfaction by choosing the transformational leadership style.
Keywords: Extrinsic; Intrinsic; Job satisfaction; Leadership style; Transactional; Transformational